Perceptions of mothers in Quezon City on corporal punishment - Dimayuga, Ira D.A.; Loyola, Katricia C.; Infantado, Grace Marie A. (Quezon City College of Home Economics, University of the Philippines Diliman, 2015)
ABSTRACT Corporal punishment is the most practiced method in disciplining children in their early years, especially in the Filipino setting. This research advocates empowering and years, especially in the Filipino setting. This research advocates empowering and educating Filipino mothers on positive discipline and child development, as these are the most effective interventions to eliminate corporal punishment in the Philippines. Thirty Filipino mothers in Quezon City participated in a semi-structured interview to identify the mothers' disciplining practices towards their preschool children and to determine their perceptions on corporal punishment. Situations, reasons, and effects of disciplining practices and corporal punishment, as well as the opinions of the mothers on the House and Senate Bills seeking to ban all forms of corporal punishment were discussed. Findings show that 87% of the mothers use corporal punishment, and spanking was found to be the most common form of physical punishment. Even though the mothers vary in perceptions, the long-term goal of discipline was the same, to provide what they think is best for the child.
Thesis (B.S. Family Life and Child Development)--University of the Philippines Diliman.
Keywords: Corporal punishment of children -- Philippines; Discipline of children -- Philippines